The Role of the WTO in Maintaining Global Trade Stability : Between Protectionism and Liberalization Policies - Zeis Zultaqawa; Mohamad Donie Aulia; Yaumi Sidik Ginanjar; Mohammad Husni Syam; Wahyudi Wahyudi (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The World Trade Organization (WTO) acts as the main institution in regulating the global trading system based on the principles of fairness and openness. However, in practice, protectionist challenges arising from large countries, such as in the trade conflict between the United States and China, hamper economic liberalization efforts and create instability in the global market. This study aims to analyze the effectiveness of the WTO's role in facing these protectionism challenges. The method used is normative juridical with a qualitative approach, which includes analysis of WTO regulations and policies, as well as a comparative approach to examine the impact of protectionism in several countries. Data were obtained through literature study of academic sources and relevant international legal documents. The results show that policy harmonization between the WTO and its member countries is needed to maintain the stability of the multilateral trading system. In addition, reforms to the WTO dispute settlement mechanism are crucial to make it more adaptive to global geopolitical dynamics. Developing countries are advised to improve competitiveness through market diversification and strengthening economic diplomacy to remain relevant in the changing international trade architecture.